Work hazards at workstations in the leather tanning industry using the Hazard Identification and Risk Assessment (HIRA) method - Henny, Henny; Budi, Agus Heri Setya; Aditya, Muhammad; Sumaryatno, Denmas Adityo; Mariawati, Ade Sri (Universitas Sultan Ageng Tirtayasa, 2024)
In the Indonesian manufacturing industry, potential hazards and work-related risks are prevalent, often resulting from worker negligence or unforeseen incidents. To address these issues, companies must enhance risk management strategies based on occupational safety and health principles. This study aims to identify hazards and assess work-related risks at workstations in Department C of the leather tanning industry using primary and secondary data. Primary data were collected directly from the production floor, while secondary data were obtained from company records. The risk assessment classified hazards into four categories: Extreme (E), High (H), Moderate (M), and Low (L), based on severity and likelihood. The findings identified potential physical, chemical, and ergonomic hazards, with three high-risk activities, five medium-risk activities, and two low-risk activities. To mitigate these risks, control measures such as personal protective equipment (PPE), warning signs, Material Safety Data Sheets (MSDS), and strict adherence to company regulations should be implemented. These preventive actions are expected to reduce high- and medium-risk activities to lower risk levels, ultimately minimizing workplace accidents.